THE STUDENTS PREPARATION BEFORE PRESENTATION IN THE CLASS - Rangkuti, Reni Novita Juliani; Lubis, Royan Alifia (Indonesian Journal of ELT and Applied Linguistics, 2024)
Effective classroom presentations require meticulous preparation to ensure successful communication and audience engagement. This mini research explores key aspects of student preparation, emphasizing the significance of thorough research, clear organization, engaging delivery, and effective practice. By conducting in-depth research, students can gather credible information and develop a strong foundation for their presentation. Organizing the content logically, using outlines, and incorporating visual aids enhances clarity and audience comprehension. Rehearsing the presentation, practicing timing, and incorporating feedback from peers or instructors can significantly improve delivery, build confidence, and minimize anxiety. Ultimately, thorough preparation empowers students to deliver impactful presentations that effectively convey their message and achieve their desired learning objectives.